EFISIENSI TEKNIS PENDIDIKAN DI KOTA SURAKARTA: APLIKASI DATA ENVELOPMENT ANALYSIS (DEA) - Muzakar Isa (Benefit: Jurnal Manajemen dan Bisnis, 2009)
The purpose of this study to analyze the factors that affect achievement in state and private high school in Surakarta in the academic year 2005/2006, and measure the level of technical efficiency of high school in Surakarta in 2006. The analytical tool used are multiple linear regression and DEA. The analytical tool used ar multiple linear regression and DEA. The results showed that 70.73 percent of high school in Surakarta is efficient, and 29.27 percent, inefficient. High schools in Surakarta on average are efficient. High school achievement in Surakarta in 2006 was influencedby student-teacher ratio, the ratio of students–administrative staff, the ratio of teacher experiencefor 15 years, the ratio of graduate teacher education, and the average value of new students NEM (score of pure national exam). English is the dominant output variables that cause inefficiencies high school in Surakarta.